(untitled) (Italian Review of Legal History, 2023)
The analysis of the rules of the Florentine Republic statutes of 1355, recently published in vernacular, offers a better understanding of the reasons of the dispute between Francesco Petrarca and Giovanni Boccaccio. The dispute revolved around the forms of the government and their requirements to guarantee well-being and freedom to their peoples. Under relentless domestic and international wars and conflicts, the institutional characters of the free Republic of Florence and of the Visconti tyranny were built. This process involved the interweaving contributions of the legal science, legislation, culture and political propaganda.